Análisis multitemporal de las coberturas agrícolas en la región Andina colombiana durante el período 2001 - 2020 (2025)
The main objective was to determine the multitemporal change of agricultural land cover in the Colombian Andean region during the period 2001-2020. For this purpose, agricultural land cover was characterized in the years 2001, 2010 and 2020 and the changes in the spatial distribution of these, between 2001-2010, 2010-2020 and 2001-2020, were established.